Rock Magnetism of the Offshore Sediments of Lake Qinghai in the Western China - Zhang, Peng; Lin, Shan; Ao, Hong; Wang, Lijuan; Sun, Xiaoyan; An, Zhisheng (Frontiers in Earth Science, 2016)
Lake Qinghai is the largest lake in China and situated in an important climate-sensitive zone on the northeastern margin of the Tibetan Plateau, making it an ideal place to study the environmental evolution of the northwest China as well as the interplay between the Asian monsoon and the westerlies in late Quaternary. In this study, detailed rock magnetic measurements were carried out on the offshore soils of Lake Qinghai. The dry grassland samples have higher magnetic susceptibility than that of the wet grassland samples, which suggests a higher concentration of magnetic minerals in the dry grassland and lower concentration of magnetic minerals in the wet grassland near the lake edge. The high concentration of the superparamagnetic (SP) magnetic minerals related to pedogenesis may also contribute to the high magnetic susceptibility of the dry grassland. The low magnetic susceptibility of the wet grassland may result from the conversion of strongly to weakly magnetic minerals and/or the dissolution of magnetic minerals. In addition, the Hm/(Gt+Hm) value has a positive correlation with the water content, thus can be taken as an effective proxy for the soil moisture.